KETERAMPILAN SISWA KELAS XI BIOLOGI DALAM MEMBUAT POSTER UNTUK MENDUKUNG PEMBELAJARAN TEKS PERSUASI DENGAN MENGGUNAKAN APLIKASI CANVA - ISYATUR RADHIYAH (STIT DARUL ULUM KOTABARU, 2024)
This research aims to find out how to use, the benefits, and the implications of Canva media for the poster writing skills of class XI students at SMA Negeri Kotabaru. The method used in this research is a descriptive qualitative method. The data source in this research was class XI Biology at Kotabaru State High School, totalling 173 students. Researchers in taking samples used purposive sampling techniques. This research involved students in classes XI Biology 1 and XI Biology 4 with a total of 69 students as sampling. The data collection techniques used in this research are observation, tests, interviews, and documentation. The results of Canva's superiority as a poster learning media for class So the advantages of Canva as a learning medium have good and effective implications for students to use in making posters.